Pengaruh Keputusan Investasi, Kebijakan Dividen, Serta Keputusan Pendanaan Terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Sartini, Luh Putu Novita; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
This study aimed to examine effect of investment decisions, dividend policy and financing decisions on firm value of manufacturing companies. This research was conducted at Indonesia Stock Exchange(BEI) with research period 2009-2011. The amount of sample using 20 companies. The sampling method used was purposive sampling method. Analysis technique used in this research was path analysis. Based on results of data analysis show that Investment decisions significant positive affects to dividend policy, Investment decisions significant positive affects to firm value, Dividend policy significant positive effect to firm value, Financing decisions significant positive affects to firm value, and Dividend policy significant positive affect to financing decisions.
Keywords: firm value, investment decision, dividend policy, financing decision